USING BAYESIAN METHODS IN THE TASK OF MODELING THE PATIENTS' PHARMACORESISTANCE DEVELOPMENT - Voronenko, Mariia A.; Zhunissova, Ulzhalgas M.; Smailova, Saule S.; Lytvynenko, Luidmila N.; Savina, Nataliia B.; Mulesa, Pavlo P.; Lytvynenko, Volodymyr I. (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
In this paper, we propose a methodology for using static Bayesian networks (BN) in modeling the development of pharmacoresistance in patients with a diagnosis of epilepsy. Methods for constructing the structure of a static BN, their parametric training, validation, sensitivity analysis and “What-if” scenario analysis are considered. The model was designed in collaboration with expert doctors, as well as expert pharmacologists in the selection and quantification of input and output variables.